In Silico Molecular Characterization of a Putative Haloacid Dehalogenase Type II from Genomic of Mesorhizobium loti Strain TONO: In Silico Molecular Characterization of a Putative Haloacid Dehalogenase Type II - Sefatullah Zakary; Hamida Mashal; Abdul Rahman Osmani; Habeebat Adekilekun Oyewus; Fahrul Huyop; Muzhgan Mohammad Nasim (Journal of Tropical Life Science, 2022)
Halogenated organic compounds are found as waste in the biosphere and can causenumerous dilemmas because of their toxicity and persistence in the environment. Theyplay a major role in the quality of life of both, human beings and other living organisms. Degradation of these compounds by microorganisms is significant to reduce recalcitrant and cost. Thus, in the current study, an in-silico approach was used for homology modelling and docking assessment of a newly identified DehLt4, type IIdehalogenase to predict its ability to degrade selected haloalkanoic acids and haloacetates. The study aimed to establish the catalytic tendencies of the enzyme to optimallydegrade the selected halogenated haloacids. The refined modelled structure of DehLt4using GROMACS 5.1.2 software revealed satisfactory scores of ERRAT (94.73%),Verify3D (90.83%) and PROCHECK (99.05 %) assessments. Active site predictionby blind docking and multiple sequence alignment indicated the catalytic triads forDehLt4 were Asp9-Lys149-Asn175. Both L-2-chloropropionic acid (L-2-CP) and trichloroacetate (TCA) docked with DehLt4 exhibited binding energy of -3.9 kcal/mol.However, the binding energy for D-2-chloropropionic acid (D-2-CP) and monochloroacetate (MCA) was -3.8 kcal/mol and -3.1 kcal/mol, respectively. Thus, the findingsof the study successfully identified the catalytic important residues of DehLt4 for possible pollutant degradation. The in-silico study as such has a good potential for characterization of newly identified dehalogenases based on basic molecular structure andfunctions analysis.Keywords: Dehalogenase, Haloacid dehalogenase, Mesorhizobium loti strain TONO,Protein structure